INVESTMENTS IN NUTRITION FOR CARDIOVASCULAR DISEASES AND TYPE 2 DIABETES - Moiseeva, Marina Viktorovna; Filimonov, Sergey Nikolaevich; Viktorova, Inna Anatolyevna; Bagisheva, Natalia Viktorovna; Trukhan, Dmitry Ivanovich (Medicine in Kuzbass, 2026)
The review article presents the results of an analysis of the main problems in modern nutrition concerning cardiovascular diseases and type 2 diabetes, describing indicators of diet quality and cardio-metabolic disorders, as well as cardiovascular risks. The general requirements and principles of healthy eating are examined in detail, not only from the standpoint of the macronutrient but also the micronutrient composition of the daily diet. This is presented within the context of the need to cultivate both a food culture and timely, rational investment in nutrition for the prevention of cardiovascular diseases and type 2 diabetes.
Keywords: nutrition; diet quality; cardiovascular diseases; type 2 diabetes; prevention